Video quality measurement using digital watermarking - Wang, Sha (University of Ottawa (Canada), 2005)
A 3-level DWT (Discrete Wavelet Transform) based objective video quality measurement method is proposed based on semi-fragile digital watermarking. The watermark is embedded into the luminance components of the Intra frames of an MPEG-2 video stream, which can be treated as images. The degradation of the watermark is used to estimate the degradation of the cover work. A quantization method is used to embed the watermark. In the watermark embedding process, 10 quantization parameters are assigned to the 10 DWT decomposed blocks which are obtained by applying 3-level DWT to the target image. And the watermark is embedded with its vulnerability adjusted according to the different frequency distribution of the content of the cover work. Automatic control is used to adjust the watermark vulnerability which is controlled by the watermark bit portions and the quantization parameters. By referring to the ideal mapping curve which is the pre-calculated relationship between the quality in terms of the classical metrics and the True Detection Rates (TDR), the TDR and quality measurement (PSNR/wPSNR/Watson JND) relationship curve of any test image can be converged to the ideal mapping curve so that the quality of the degraded image can easily measured by checking the ideal mapping curve with the TDR computed during the watermark extraction. The TDR is calculated between the original watermark and the degraded watermark. After the watermark extraction, the degradation of the extracted watermark is used to estimate video/image quality in terms of the classical metrics. By comparing the video quality estimated by the proposed method with the calculated quality in terms of PSNR, wPSNR, and JND, it is clear that the proposed method can be used to evaluate video quality against compression with high accuracy.
Keywords: Engineering, Electronics and Electrical.